Occupational noise exposure at sea: A socio-legal study on fish harvesters’ perceptions in Newfoundland and Labrador, Canada - Yadav, Om Prakash; Shan, Desai; Sarkar, Atanu; Moro, Lorenzo (Frontiers in Public Health, 2023)
Introduction: Noise is a significant health hazard for fish harvesters. Chronic exposure to hazardous noise levels of 85 dB(A) for an 8-hour work shift can have adverse health impacts, including both auditory and non-auditory health problems such as noise-induced hearing loss, stress, hypertension, sleeping disorders, and impaired cognitive performance. Methods: A review of legislation and policies governing workplace noise exposure, as well as qualitative, semi-structured interviews, were conducted to assess how fish harvesters in Newfoundland and Labrador (NL) manage onboard occupational noise exposure and perceive noise-induced health problems, as well as the barriers and challenges associated with preventing and controlling noise exposure. Results: The legal review shows no compulsory noise preventive measure at the fishing vessel design stage in Canada. Limited implementation of Occupational Health and Safety (OHS) regulations to control and prevent onboard noise by employers in Newfoundland and Labrador. Fishers reported that their workplace is noisy. Over time, fish harvesters adapted to the environment and learned to tolerate loud noise, displaying fatalistic behaviour. Fish harvesters reported avoiding using hearing protection onboard due to navigation safety concerns. Fishers reported hearing loss as well as other non-auditory health problems. Inadequate noise control measures adopted by employers, a limited supply of hearing protection onboard, and a lack of regular hearing testing, training, and education were identified as the main barriers to preventing and controlling noise exposure. Conclusions: Proper implementation of NL OHS regulations and the development of hearing conservation initiatives by employers are necessary. All stakeholders, including the federal and provincial governments, WorkplaceNL, and not-for-profit fishing organizations in the province, are strongly recommended to initiate training and education campaigns to help fish harvesters understand noise exposure and adopt preventive measures.